The Effects of Using Google SketchUp on the Mental Rotation Skills of Eighth Grade Students - Erkoc, Mehmet Fatih; Gecu, Zeynep; Erkoc, Cigdem (EDAM, 2013)
The aim of this study is to investigate the effectiveness of Google SketchUp, which is a computer aided design (CAD) software, on the Mental Rotation Skills of eighth grade students. For this purpose, in the spring semester of the 2011-2012 academic year, a treatment was conducted with 62 students comprised of 8A and 8B classes in the GSD Education Foundation Bahcelievler Primary School during the six weeks. The study was carried out in accordance with a quasi-experimental research with pretest and posttest design. The Vandenberg Mental Rotation Test was used to determine mental rotation skills of the students, participating the research study, as a pretest and posttest. When pretest results examined with independent samples t-test, a significant difference was found in favor of the class 8B ((x) over bar (8A) = 5.42 (x) over bar (8B) = 8.45 t(60)=3.62, p .05).
Keywords: Spatial Ability; Mental Rotation; Google Sketchup; Concrete Objects; Manipulative; SPATIAL VISUALIZATION SKILLS; DYNAMIC GEOMETRY SOFTWARE; MANIPULATIVES; INSTRUCTION; ORIENTATION; ABILITY; Education & Educational Research